A Study of Inflammatory/Necrosis Biomarkers in the Fracture of the Femur Treated with Proximal Femoral Nail Antirotation. (14th May 2015) - Marino, Mariapaola; Palmieri, Giuseppe; Peruzzi, Marco; Scuderi, Flavia; Bartoccioni, Emanuela
Abstract : Pertrochanteric fractures are common injuries in adults and source of morbidity and mortality among the elderly. Different surgical techniques were recommended for their treatment but undoubtedly they add an additional inflammatory trauma along the fracture itself. Many attempts to quantify the degree of approach-related trauma are carried out through measurements of systemic inflammatory parameters. In this study we prospectively analyzed laboratory data of 20 patients over eighty with pertrochanteric fracture of the femur treated with proximal femoral nail antirotation (PFNA). This is an excellent device for osteosynthesis because it can be easily and quickly inserted by a mini-incision providing stable fixation and early full mobilization. Serum tumor necrosis factor-alpha (TNF- α ), interleukin-6 (IL-6), C-reactive protein (CRP), and plasma creatin kinase (CK) were evaluated 1 hour preoperatively and 24 hours postoperatively. Our results show that PFNA did not induce significant increments in serum levels of inflammatory cytokines TNF- α and IL-6; CRP was elevated preoperatively in correlation with waiting time for surgery; CRP and CK showed a significant increment in the first postoperatory day; CK increment was correlated with surgical time length. We conclude that, for the markers we analyzed, PFNA shows a low biomechanical-inflammatory profile that represents an advantage over other techniques.